Mídia e segurança pública no Brasil: o Jornal Nacional e a securitização da intervenção federal no Rio de Janeiro (2018) - Schneider, Gabriela (2023)
This doctoral dissertation has as its central theme the media and public security in Brazil. The study is justified taking into account that the issue of securitization of public security generates concern in society and also requires attention from news coverage. In order to study the aforementioned articulation, the research problem asks: how does newsworthiness fit into the process of securitization of public security in Brazil? It is argued that newsworthiness is part of the securitization process of public security in Brazil in a more decisive way than predicted by current securitization theories, which classify media actions predominantly as representatives of the audience of this process. The insertion of the media in the purposes of public security occurs from its commitment to the social values inherent in the securitization process and it does so from an understanding that is its own. In the Brazilian case, we understand that the media assumes the condition of securitizing agent of its own will and relatively autonomous in the scope of public security of the national State. The general objective of the research is to understand the phenomenon of media discursivity put into circulation with a view to affecting the process of securitization of public security in Brazil. In this sense, the specific objectives are: (i) evaluate the conception of media and audience in securitization theories; (ii) study the phenomenon of newsworthiness in the circulation of meanings related to television news coverage in public security; (iii) evaluate newsworthiness centered on the circulation of fear narratives for the purposes of securitization theory; (iv) recover salient aspects of the securitization of public security in Brazil, with emphasis on mentions (or not) of news coverage of Law and Order (GLO) operations and others; and (v) analyze the characteristics of the televisual discursivity and the effort to produce the own meaning of the Jornal Nacional of Rede Globo de Televisão in the two weeks that preceded the signing of the decree and the actual execution of the Federal Intervention in Rio de Janeiro 2018. The phd dissertation seeks to advance in dialogues with phenomena that have been partially studied in the field of Law, International Relations and Journalism, evaluating cases of application and test in Brazil. The results of the empirical analysis of news coverage carried out by Jornal Nacional on Rede Globo de Televisão were produced considering the methodological proposition for investigating televisual texts, which is based on European discursive semiotics. The interpretation of the analysis shows that there was a directing of the Jornal Nacional to the narratives of fear and the exacerbation of the feeling of insecurity of the population in the fifteen days that preceded the Federal Intervention in Rio de Janeiro. The policy of fear, when used in journalistic coverage, in order of established newsworthiness, ignores the context of a given situation and ends up inducing the need for urgent measures in favor of legitimizing coercive and militarized government responses adopted to the detriment of others, a typical phenomenon of securitization processes.